2017
DOI: 10.1542/peds.2016-2943
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Breastfeeding on Dental Caries: A Population-Based Birth Cohort Study

Abstract: Prolonged breastfeeding increases the risk of having dental caries. Preventive interventions for dental caries should be established as early as possible because breastfeeding is beneficial for children's health. Mechanisms underlying this process should be investigated more deeply.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
117
2
13

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(140 citation statements)
references
References 37 publications
8
117
2
13
Order By: Relevance
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study were in accordance with several previous studies [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017]. In Japan, "no residence tax" means low household income.…”
Section: Discussionsupporting
confidence: 92%
“…Some previous studies in developing countries reported that risk factors associated with S-ECC were frequent or prolonged breastfeeding [Özen et al, 2016;Feldens et al, 2018], socioeconomic status [Schroth et al, 2013a;Li et al, 2017;Peres et al, 2017], not having help with brushing [Turton et al, 2016;Mangla et al, 2017], and snacking habits [Evans et al, 2013;Mangla et al, 2017;Peres et al, 2017;Sun et al, 2017]. However, it is unclear whether these risk factors for S-ECC are similarly associated with S-ECC in developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the novelty of the statistical approach (MSMs) used to assess the CDE, as well as the multiple imputation technique adopted to handle missing data, should be acknowledged. An advantage of MSM over conventional methods is that by dealing with potential confounding through a weighting process rather than using conventional conditional regressions, MSMs reduce the bias of conventional approaches …”
Section: Discussionmentioning
confidence: 99%
“…The association between feeding method and ECC is pretty intricated and involves in a variety of factors including the frequency, duration, numbers, time and formula of the feeding. Previous studies ever reported that the breastfeeding and its duration is not associated with the ascended risk of ECC [13], yet studies also found that both prolonged breastfeeding and high-frequency feeding in late infancy augments the risk of having dental caries [26,27]. Van Palenstein et al [28], interestingly, reported that breastfeeding during the daylight beyond the age of 12-month was not associated with ECC for 25-to 30-month old infants, the relevant factor is breastfeeding at night > 2 times, and exposing > 15 minutes per nocturnal feeding.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%
“…Limitations include the issues in the OHC knowledge and attitude designed for the questionnaire 15 are relatively basic and traditional. Several major risk factors are incorporated in current study, but unlike those monographic researches which excavated and explored sufficient detailed information about one certain targeting factor associated with ECC [27,31,50]. We have to say that some data on detailed information is limited, such as frequency of bedtime feeding, brushing efficiency, floss assist status, cariogenic microbial flora, each of which is reported to be associated with ECC.…”
Section: Logistic Regression Analysesmentioning
confidence: 99%